Well-being in the Czech Republic in an Aggregate Perspective - Kamila Fialová; Pavel Štika (Review of Economic Perspectives, 2015)
The article assesses well-being in the Czech Republic compared to other Visegrad countries (Slovakia, Hungary, Poland) and neighbouring Germany and Austria. By employing various approaches designed by several international organisations it takes an aggregate perspective to assess both the current well-being and its sustainability into the future. All employed indicators that relate to current well-being evaluate the well-being in the Czech Republic as moderate among the OECD countries. The results indicate that the position in well-being rankings improves with the growing number of dimensions or subjective factors included in the well-being measure, mainly due to the reduction in relative importance of income dimension and higher emphasis on the multidimensionality and complexity of well-being. In the case of sustainability, large differences can be identified in evaluation stemming from Happy Planet Index and Sustainable Society Index perspective. Although both of them agree on unfavourable situation as regards environmental sustainability in the Czech Republic, different accent on economic area alters the final result substantially. The analysis shows that for any well-being assessment, the choice of indicators is crucial and a large portion of caution is necessary when interpreting these.
Keywords: 330